2015
DOI: 10.24006/jilt.2015.13.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Operational Efficiency of Major Airlines in Asia-Pacific Region

Abstract: This paper uses various Data Envelopment Analysis (SBM-DEA) approaches to study the efficiency of major airlines in Asia-Pacific region. To evaluate the operation efficiency of fourteen major airlines in Asia-Pacific region from 2003-2011, Available Seat Kilometers(ASK), Available Ton Kilometers(ATK), the number of employees are used as input factors, Revenue Passenger Kilometers(RPK), Revenue Ton Kilometers(RTK), the amount of Sales are used as output factors. The non-radial SBM-DEA (Slacks-based Measure of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Chang and Lee (2014) used an SBM DEA model to assess the operational performances of 27 airlines in 2010 and explore the impact of the economic and environmental efficiencies on airline operations and found that Asian airlines were more efficient than European or American airlines. Gong and Kim (2015) used a dynamic SBM model to assess the operational performances of 14 major airlines in the Asia Pacific region from 2003 to 2011, finding that the South Korean and Japanese Airlines were the most efficient and could be used as benchmark airlines. Jain and Natarajan (2015) used DEA and an input efficiency profiling (IEP) model to assess the service and technical efficiencies in 12 major Indian airlines from 2006 to 2010 and found that the low‐cost airlines and the larger and smaller state‐owned airlines were more efficient than the private airlines and that the state‐owned airlines were more productive even though they suffered economic losses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang and Lee (2014) used an SBM DEA model to assess the operational performances of 27 airlines in 2010 and explore the impact of the economic and environmental efficiencies on airline operations and found that Asian airlines were more efficient than European or American airlines. Gong and Kim (2015) used a dynamic SBM model to assess the operational performances of 14 major airlines in the Asia Pacific region from 2003 to 2011, finding that the South Korean and Japanese Airlines were the most efficient and could be used as benchmark airlines. Jain and Natarajan (2015) used DEA and an input efficiency profiling (IEP) model to assess the service and technical efficiencies in 12 major Indian airlines from 2006 to 2010 and found that the low‐cost airlines and the larger and smaller state‐owned airlines were more efficient than the private airlines and that the state‐owned airlines were more productive even though they suffered economic losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Global aviation deregulation made the aviation industry more competitive and led to increased mergers, acquisitions, and alliances by the larger international airlines, which increased the research focus on aviation efficiency and productivity (Barbot et al, 2008; Barros et al, 2013; Chang & Lee, 2012; Chen & Chiou, 2006; Chow, 2010; Cui et al, 2016; Greer, 2009; Gong & Kim, 2015; Hu et al, 2017; Inglada et al, 2006; Jain & Natarajan, 2015; Lee & Worthington, 2014; Li et al, 2015, 2016; Mallikarjun, 2015; Martín & Román, 2006; Merkert & Pearson, 2015; Mhlanga, 2018; Omrani & Soltanzadeh, 2016; Ouellette et al, 2010; Pacheco & Fernandes, 2003; Scheraga, 2004; Tan & Chen, 2011; Tavassoli et al, 2014; Wanke & Barros, 2016; Wu et al, 2013; Wu & Liao, 2014; Yu et al, 2016; Żółtaszek & Pisarek, 2016; Zhu, 2011), with some studies examining the advantages and disadvantages of global strategic aviation alliances. For example, Varadarajan and Cunningham (1995) examined whether alliance operations reduced costs, Eisenhardt and Schoonhoven (1996) found that the shared resources available to alliances increased profit, and Porter and Fuller (1986) assessed whether strategic alliances reduced market risk; however, some studies (Hamel et al, 1989; Robinson, 1988; Williamson & Ouchi, 1981) found that strategic alliances had negative impacts on business operations.…”
Section: Introductionmentioning
confidence: 99%